2021
DOI: 10.1186/s12864-021-08183-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional deciphering suggested the regulatory roles of long intergenic ncRNAs (lincRNAs) in increasing grafting pepper resistance to Phytophthora capsici

Abstract: Background As a popular and valuable technique, grafting is widely used to protect against soil-borne diseases and nematodes in vegetable production. Growing evidences have revealed that long intergenic ncRNAs (lincRNAs) are strictly regulated and play essential roles in plants development and stress responses. Nevertheless, genome-wide identification and function deciphering of pepper lincRNAs, especially for their roles in improving grafting pepper resistance to Phytophthora capsici is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Then, miRNA and CsDUF966 CDS sequences were submitted to the online tool psRNATarget with default parameters ( , accessed on 18 June 2022) [ 45 , 46 ]. The targeting relationships of miRNA to CsDUF966 were further visualized by R package ‘ggalluvial’ [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, miRNA and CsDUF966 CDS sequences were submitted to the online tool psRNATarget with default parameters ( , accessed on 18 June 2022) [ 45 , 46 ]. The targeting relationships of miRNA to CsDUF966 were further visualized by R package ‘ggalluvial’ [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The differentially expressed pepper lncRNAs in response to P . capsici were found to increase pepper resistance to soil-borne diseases by interacting with their coordinated miRNA-mRNA and regulating the expression of disease-defense–related genes [ 213 ] ( Fig 3D and Table 1 ). Genes encoding zinc finger proteins, pentatricopeptide repeat-containing proteins, and LRR receptor-like serine/threonine-protein kinases are potentially regulated by lncRNAs to regulate plant immune responses to P .…”
Section: Main Contentmentioning
confidence: 99%
“…Genes encoding zinc finger proteins, pentatricopeptide repeat-containing proteins, and LRR receptor-like serine/threonine-protein kinases are potentially regulated by lncRNAs to regulate plant immune responses to P . capsici [ 213 ]. On the other hand, the expression levels of lncRNAs in oomycetes were also altered during their infection of plant.…”
Section: Main Contentmentioning
confidence: 99%
“…Grafting alters the expression of miRNA and its target genes, indicating that miRNA plays an important role in regulating the physiological process of grafted seedlings at a post-transcriptional level ( Khaldun et al, 2016 ; Li et al, 2016 ; Kehr and Kragler, 2018 ). In recent years, a large number of grafting-related miRNAs have been obtained by sRNA-Seq technology ( Pagliarani et al, 2017 ; Yin et al, 2021 ; Hu et al, 2022 ). In our previous study on cucumber/pumpkin grafting compatibility, we isolated and identified 60 differentially expressed miRNAs in scions of grafted seedlings through high-throughput sequencing, but no specific miRNA was found ( Ren et al, 2018 ), suggesting that the rootstock regulated a series of physiological characteristics mainly by inducing differential expression of miRNA inherent in the scion.…”
Section: Introductionmentioning
confidence: 99%